Exploring Fear of Negative Evaluation in Foreign Language Anxiety: Photovoice of Undergraduates in Speaking Class - Wardhani, Anindyastuti (JSSH (Jurnal Sains Sosial dan Humaniora), 2019)
Foreign Language Anxiety (FLA) is a common situation happens in EFL classroom. This phenomenon usually causes the students’ anxiety while they are learning English. The previous study proved that language learners performed significantly better on oral foreign language if they were in less anxious situations. Students’ unwillingness for participating speaking activities in the classroom caused by their assumption of being judged negatively and lack of mastering the speaking skill. The objective of this research is to explore whether there is foreign language anxiety problem among Indonesian undergraduates in speaking class. The researchers collected and processed the data using Photovoice. The participants of this research were 14 undergraduate students in the 5th semester. The findings indicated that the students have anxiety during performing speaking activity in classroom. As the implication, teachers can facilitate the students by creating a conducive, comfortable, and non-threatening class to help alleviating the students' foreign language anxiety.